Replacement names for two nematode junior homonyms - Bernard, Ernest C.; Phillips, Gary (Zootaxa, 2015)
During taxonomic investigations of nematodes that parasitize millipedes, we reviewed the literature on the nematode genus Robertia Travassos & Kloss, 1961. This literature search also revealed the existence of two other identical genus-group names for taxa in Chordata and Arthropoda: Robertia Boonstra, 1948 (extinct Permian non-mammalian synapsid) and Robertia Saaristo, 2006 (theridiid spider from the Seychelles), respectively. Of these three homonyms, Robertia Boonstra, 1948 clearly has priority. The spider name Robertia recently was replaced with Seycellesa Kocak & Kemal, 2008. The nematode genus-name also is a junior homonym and requires replacement. We propose the new replacement name Traklosia for Robertia Travassos & Kloss, 1961.